Electrochemical studies on the corrosion behaviour of Aluminium in an alkaline medium - Palanichamy Satyabama; Nellainayagam Narendran; Karuyppiah Bavithra Devi; Thiruppathi Raja Uma Sankareswar; Anita Nilavan; Susai Rajendran; Caslav Lacnjevac (Zaštita Materijala)
Corrosion of Aluminum metal at pH 10 has been controlled by dicarboxylic acids such as oxalic acid (OA) and adipic acid (AA).The Inhibition efficiency (IE) has been determined by the classical weight loss method. The maximum inhibition efficiency (IE) offered by the oxalic acid (OA) and adipic acid (AA) 250 ppm and Zn2+ 50 ppm system are 88 and 96%. To determine the values of Linear Polarization Resistance (LPR) and corrosion Current (Icorr), potentiodynamic polarization study has been used.